Single intra‐articular dexamethasone injection immediately post‐surgery in a rabbit model mitigates early inflammatory responses and post‐traumatic osteoarthritis‐like alterations. Issue 12 (7th July 2015) - Heard, Bryan J.; Barton, Kristen I.; Chung, May; Achari, Yamini; Shrive, Nigel G.; Frank, Cyril B.; Hart, David A.
ABSTRACT: Despite surgical reconstruction of the anterior cruciate ligament, a significant number of patients will still develop post‐traumatic osteoarthritis (PTOA). Our objective was to determine if mitigating aspects of the acute phase of inflammation following a defined knee surgery with a single administration of a glucocorticoid could prevent the development of PTOA‐like changes within an established rabbit model of surgically induced PTOA. An early and late post‐surgical time‐point was investigated in this study (48 h and 9 weeks post‐surgery) in which the following groups were repeated (each n  = 6, for a total of 24 rabbits per time‐point, and 48 rabbits used in the study): control (age/sex matched), sham (arthrotomy), drill injury (arthrotomy + two drill holes to a non‐cartilaginous area of the femoral notch), and drill injury + single intra‐articular (IA) injection of dexamethasone (DEX). At 48 h post‐surgery, DEX treatment significantly lowered the mRNA levels for a subset of pro‐inflammatory mediators, and significantly lowered the histological grade. Nine weeks post surgery, DEX treatment significantly lowered the histological scores (presented as effect size) for synovium (3.8), lateral femoral condyle (3.9), and lateral tibial cartilage (5.1) samples. Thus, DEX likely acts to prevent injury induced inflammation that could contribute to subsequent joint damage. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1826–1834, 2015.